1987
DOI: 10.1093/nar/15.17.6843
|View full text |Cite
|
Sign up to set email alerts
|

The effects of covalent additions of a psoralen on transcription byE. coliRNA polymerase

Abstract: Synthetic DNA substrates containing a site-specifically engineered psoralen monoadduct or diadduct were used to characterize the response of the E. coli RNA polymerase elongation complex to these lesions. The psoralen derivative HMT (4'-hydroxymethyl-4,5', 8-trimethylpsoralen) was site specifically placed into two synthetic double-stranded DNA fragments each of which contained an E. coli RNA polymerase promoter at one end. The HMT molecule was attached to the middle of the DNA fragments as either a furan-side … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
35
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 45 publications
4
35
0
Order By: Relevance
“…Formation ofpsoralen photoproducts (15)(16)(17), as well as a stable triplex on a duplex target, has been shown to inhibit transcription (18,19). On a single-stranded nucleic acid, triplex formation might be expected to be more efficient in arresting biological processes than formation of a double helix with an antisense oligonucleotide.…”
Section: Resultsmentioning
confidence: 99%
“…Formation ofpsoralen photoproducts (15)(16)(17), as well as a stable triplex on a duplex target, has been shown to inhibit transcription (18,19). On a single-stranded nucleic acid, triplex formation might be expected to be more efficient in arresting biological processes than formation of a double helix with an antisense oligonucleotide.…”
Section: Resultsmentioning
confidence: 99%
“…Human excision nuclease releases excised oligomers from gapped duplex. The 3Ј-terminally biotinylated, internally radiolabeled cholesterol-A substrate 156 nucleotides in length Shi et al, 1987) was incubated with E. coli or human excision nuclease. The DNA was then pulled down with streptavidin beads, and the streptavidin bead-bound (B) and -unbound (U) fractions were analyzed on a sequencing gel.…”
Section: Discussionmentioning
confidence: 99%
“…Toward this goal, Selby and Sancar (37) adapted the transcription-repair template/substrate system of Shi et al (42) to the study of thymine dimer (T< >T) repair in a defined system. It was found that a T< >T in the coding (nontranscribed) strand had no discernible effect on transcription.…”
Section: Introductionmentioning
confidence: 99%